Can warming-up or stretching be dispensed with before performing physical power or aerobic exercises? - Xavier Claudino, Talita; Fett, Carlos Alexandre; Fett, Waléria Christiane Rezende (Revista Brasileira de Educação Física e Esporte, 2023)
The activities in preparation for physical exercise and/or sporting competitions are performed with a view to improving performance and preventing lesions. Traditional Warm-up (TW), such as jogging and Proprioceptive Neuromuscular Facilitation (PNF) stretching, are two examples of activities used for this purpose. However, there is no consensus in the literature about their efficacy, and which of them is the best. The aim is to compare the effects of TW and PNF on anaerobic power (AnP) and Aerobic Power (AP) and on physiological variables. This study evaluated 10 (ten) men between the ages of 18 and 30 years, physically active, non-athletes, in an outdoor environment with a mean temperature of 34º C, at 04 different time intervals, performing TW (M1), PNF (M2), TW (M3) and PNF (M4) before the long jump and 20m back and forth tests, with an interval of one week between them. The AnP and AP values were calculated; the post-test lactate level, cardiac frequency were measured, and the volunteers were asked about late pain 24h the tests. One-way ANOVA was used for the 04 time intervals, with significance established at 5%. There were no differences between the variables in the different time intervals. There was no difference in physical performance in any of the types of pre-exercise preparation activities. Furthermore, TW with elevation of body temperature and PNF appeared to be dispensable for active youngsters in a warm environment.